2018
DOI: 10.22336/rjo.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

Leber’s hereditary optic neuropathy - Case report

Abstract: Leber's hereditary optic neuropathy is the most common mitochondrial condition and is characterized by bilateral, painless, subacute visual loss that develops during young adult life. LHON is a rare condition and this lack of knowledge can make doctors suspect and treat for other causes of vision loss. Typically, a series of tests are performed to confirm LHON diagnosis or exclude any other conditions. We presented the case of two brothers, HB, of 40 years old and HF, of 38 years old, who presented with a decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Inglese et al showed that optic nerve volume, mean diffusion and Magnetization Transfer Ratio measures were changed in LHON [34]. Iorga et al showed that optic nerve volumes measured on 3D T1-weighted images were lower in two familial cases of LHON [35].…”
Section: Introductionmentioning
confidence: 99%
“…Inglese et al showed that optic nerve volume, mean diffusion and Magnetization Transfer Ratio measures were changed in LHON [34]. Iorga et al showed that optic nerve volumes measured on 3D T1-weighted images were lower in two familial cases of LHON [35].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety of idebenone was assessed by Klopstock et al in 2011 in the RHODOS study [12,19,[26][27][28]. The experts' consensus of idebenone recommends that the treatment should start in the first year from visual loss onset (in the acute stage), as early as possible, the administration of the idebenone dose of 900 mg/ day being given into three daily doses of 300 mg with meals [12,29]. Treatment should be given for at least 12 months to assess a therapeutic response, then discontinuation of the drug should be considered after 12 months once a plateau recovery is reached, or no improvements are observed [12,29].…”
Section: Therapeutic Options In Lhonmentioning
confidence: 99%
“…The experts' consensus of idebenone recommends that the treatment should start in the first year from visual loss onset (in the acute stage), as early as possible, the administration of the idebenone dose of 900 mg/ day being given into three daily doses of 300 mg with meals [12,29]. Treatment should be given for at least 12 months to assess a therapeutic response, then discontinuation of the drug should be considered after 12 months once a plateau recovery is reached, or no improvements are observed [12,29]. Two others multicenter studies (LEROS and PAROS) were launched after the idebenone commercial approval, being designed to assess the long-term efficacy and safety of the drug [12].…”
Section: Therapeutic Options In Lhonmentioning
confidence: 99%
“…We read with interest about two brothers with Leber’s hereditary optic neuropathy (LHON) due to the ND1 variant m.3460G>A by Iorga et al [ 1 ]. We have the following comments and concerns.…”
mentioning
confidence: 99%
“…Another inadequacy of the study is that no family screening for the pathogenic variant had been carried out [ 1 ]. Accordingly, we do not know who else in the family carried the mutation.…”
mentioning
confidence: 99%